Glory [videorecording (DVD)] - Grozeva, Kristina, 1976-; Gosheva, Margita; Denoli͡ubov, Stefan, 1968-; Todorov, Kitodar, 1974- (Film Movement series, 2017)
"Tsanko Petrov, a railroad worker, finds millions of leva [Bulgarian currency] on the train tracks. He decides to turn the money over to the police, for which the state rewards him with a new wristwatch that soon stops working. Meanwhile, Julia Staikova, head of the PR department of the Ministry of Transport, loses Petrov's old watch, a family relic. Here starts his desperate struggle to recover both his old watch and his dignity."--Publisher's website.